(untitled) (Islamic Sciences Journal, 2025)
This research explores the life of Al-Farabi (may Allah have mercy on him) and the mawquf (suspended or attributed to companions) hadiths documented in his work Diwan al-Adab. The study employs an inductive-analytical methodology in examining both his biography and the hadiths. A total of (2 ) hadiths were analyzed, following scientific principles of hadith criticism and authentication. The study reveals that Al-Farabi’s Diwan al-Adab includes a substantial number of noble Prophetic traditions that warrant rigorous scrutiny and academic attention. Like other classical linguistic works, Al-Farabi’s book contains some weak narrations, emphasizing the need for scholarly review and clarification for readers. The research structure begins with an introduction addressing the significance of the topic, the reasons behind its selection, previous studies in the field, and the adopted methodology, and it is organized as the following; The first section is dedicated to his personal life, while the second focuses on his scholarly contributions